Vagabond fictions : gender and experiment in British women's writing, 1945-1970 - Sweeney, Carole (Edinburgh University Press, 2020)
Filling in a blank spot in the history of twentieth-century women's writing, Carole Sweeney examines the work of five experimental writers, whose writing has been neglected in accounts of the development of post-1945 British literature.